Breaking Taboos: Syrian Women Reshaping Gender Roles in Zarqa, Jordan - Qonaish, Farah (AUC Knowledge Fountain, 2025)
This research explores the changes in gender roles among Syrian refugee women in Jordan. Since 2011, more than a million Syrian refugees have settled in Jordan. Around 83% of Syrian refugees have resided in host communities in Jordan and around 70% of the Syrian population come from the rural areas in Syria refugees. Syrian refugees have experienced change on different levels of their lives since the beginning of the displacement. This ethnographic study was conducted in Zarqa, a major city in the middle region of Jordan, and a major host community for Syrian refugees in Jordan. The city is known for the high poverty, high population density, and diverse religious and ethnic groups. Hence, this research contributes in presenting different refugee experiences in Zarqa for five refugee women from different ages and backgrounds, along with an ethnographic analysis of the Syrian refugee community using group discussions and participant observations in Zarqa. Moreover, Syrian refugees’ experiences were analyzed according to their regional, educational, age, and gender backgrounds, which contributed to understanding the changes that different stories present. As Syrian women had increased access to education, employment, and mobility, they adopted new roles in the process. In summary, this research contributed to the literature that tackles gender roles and displacement on the macro level of social and economic structures, while at the same time analyze individual refugee experiences on the micro level.